AQ-6 Detection of Brucella abortus in Beef Cattle which Transported Via Kendari Agricultural Quarantine in 2017 - N Rifqiyah; A I Pratomo; A Novianjaya; A Karyono (Hemera Zoa, 2018)
Brucellosis on cattle is mainly caused by Brucella abortus. Beside cattle, the bacteria is also able to infect other ruminants like buffalo, camel, swine, sheep, and goat. Brucella bacteria have nine biotypes causing similiar disease. The disease may lead to abortion which resulting in high economic losses. Brucellosis can be transmitted via oral and nasal. The source of infection are mainly plasenta and fetal fluid from infected cattle which contaminating feed and drinking water. A cattle farm may become infected from the introduction of new cattle from outside, whether it is male, female, calf, or adult cattle. In pregnant cow, Brucella abortus will develop rapidly because of the presence of erythritol, a type of carbohydrate which act as growth stimulant for Brucella abortus. It is commonly found in chorion, cotyledon, or fetal fluid. The Province of Southeast Sulawesi had a population of 331,958 cattle in 2016. The cattle is routinely transported to its neighbor province, South Sulawesi. In 2017, the cattle is transported 219 times with a total number of cattle of 3,038.